Studi Tentang Pembelajaran Kimia di SMAN 1 Narmada di Tengah Wabah Covid-19 Tahun Pelajaran 2020 - Syahraini, Nurul; Muntari, Muntari (FKIP University of Mataram, 2024)
This study aims to describe the planning, implementation, and obstacles to learning chemistry during COVID-19 at SMAN 1 Narmada school year 2020. This type of research is descriptive, using qualitative and quantitative approaches. The sampling technique used non-probability sampling with a purpositive sampling type. Retrieval of data about students’ chemistry learning using a questionnaire and the teacher by conducting interviews. The data analysis technique is done by calculating the percentage of the results obtained: the planning teacher prepares a new RPP to adapt to the learning situation by changing some aspects of the RPP. The implementation, in a row, preliminary activities, core activities, and closing activities of 73%, 70%, and 72% are included in the criteria of good enough. Chemistry learning obstacles of 83% included in the very high category.